La carne in Tolstoj e Dostoevskij: Slavic Sins of the Flesh di Ronald D. LeBlanc (ENTHYMEMA International journal of literary criticism, literary theory, and philosophy of literature, 2010)
Recensiamo il saggio di Ronald D. LeBlanc, Slavic Sins of the Flesh: Food, Sex, and Carnal Appetite in Nineteenth-century Russian fiction,  University  of New Hampshire Press, Durham, 2009.